Molecular spinning top: visualizing the dynamics of M3N@C80 with variable temperature single crystal X-ray diffraction. Issue 86 (14th October 2019) - Liu, Fupin; Spree, Lukas
Abstract : The temperature dependent rotation of Ho2 LuN and Lu3 N within a C80 fullerene cage has been visualized. Abstract : Variable temperature X-ray diffraction studies on two single crystals containing M3 N@C80, i.e., Ho2 LuN@C80 ·NiOEP·2(C6 H6 ) and Lu3 N@C80 ·NiOEP·2(C6 H6 ), (NiOEP = Nickel octaethylporphyrin) unravelled the temperature dependent rotation of the M3 N cluster and C80 cage on the static NiOEP molecule.